Karakterisasi Fisikokimia Sistem Biner Siprofloksasin HCl – PEG 4000 - Resva Meinisasti; Auzal Halim; Erizal Zaini (Jurnal Sains Farmasi & Klinis, 2015)
"Physicochemical Characterization of Binary Systems Ciprofloxacin HCl - PEG 4000" has been reseach. This study aimed to characterize ciprofloxacin HCl formula that was developed to 9, with a comparison between ciprofloxacin - PEG 4000 following formula I (1: 9), formula II (2: 8), formula III (3: 7), formula IV (4: 6), formula V (5: 5), formula VI (6: 4), formula VII (7: 3), formula VIII (8: 2) and formula IX (9: 1). Binary system made by the manufacture of solid dispersion by melting method. The results of the binary System were characterized by analysis Differential Thermal Analysis (DTA), X-ray diffraction, IR spectrophotometry, and Scanning Electron Microscope (SEM). The results of this analysis have results of the binary solid dispersion systems a good formula this VII.